Centile charts for birthweight for gestational age for Scottish singleton births - Jarvis Stephen; Greer Ian; Gray Ron; Chalmers James; Bonellie Sandra; Williams Claire (BMC, 2008)
Abstract Background Centile charts of birthweight for gestational age are used to identify low birthweight babies. The charts currently used in Scotland are based on data from the 1970s and require updating given changes in birthweight and in the measurement of gestational age since then. Methods Routinely collected data of 100,133 singleton births occurring in Scotland from 1998-2003 were used to construct new centile charts using the LMS method. Results Centile charts for birthweight for sex and parity groupings were constructed for singleton birth and compared to existing charts used in Scottish hospitals. Conclusion Mean birthweight has been shown to have increased over recent decades. The differences shown between the new and currently used centiles confirm the need for more up-to-date centiles for birthweight for gestational age.